A Bibliometric Analysis of the Knowledge Exchange Patterns Between Major Technology and Innovation Management Journals (1999–2013)1. Issue 1 (1st December 2017) - Sarin, Shikhar; Haon, Christophe; Belkhouja, Mustapha
Abstract : This essay takes a longitudinal look at the knowledge flow patterns between major technology and innovation management (TIM) journals and the effect on their impact factors. We analyze the flow of 29, 776 citations from 4171 articles published in the top six dedicated TIM journals between 1999 and 2013. Findings indicate one subset of journals becoming more firmly rooted in the TIM domain, while the others becoming increasingly insulated from it. JPIM displays peculiar knowledge flow patterns, suggesting a broadening of its knowledge base and impact. Our bibliometric analysis provides one of the most comprehensive and detailed year‐by‐year looks at the intradomain knowledge exchange patterns over a 15‐year period.